Japanese encephalitis virus-associated human microglia induce cell death of human microvascular endothelial cells in receptor-independent infection - Fellay, Isabelle; Blanc, Pauline; Larionov, Alexey; Schlunke, Léa; Filgueira, Luis; Lannes, Nils (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe neurotropic virus Japanese encephalitis virus invades the human central nervous system, inducing neuroinflammation and further disruption of the blood-brain barrier. JEV interacts with various cell types of the blood-brain barrier including the endothelial cells. The present work aims to investigate impact of receptor-dependent and independent infection of human microvascular endothelial cells by Japanese encephalitis virus.MethodsReceptor-dependent infection was achieved using cell-free virus while receptor-independent infection was by co-culture of microvascular endothelial cells with virus-associated microglia.ResultsWhile both receptor-dependent and independent infections of human microvascular endothelial cells led to virus propagation, only receptor-independent infection induced cell death of human microvascular endothelial cells. While the CX3CR1-CX3CL1 axis was inefficient in blocking virus rescue and protecting endothelial cell from cell death, transcriptomics analysis identified Tumour Necrosis Factor-related apoptosis inducing ligand and receptors as potential key player leading to endothelial cell death.DiscussionOverall, our findings demonstrate that human microvascular endothelial cells supply virus propagation and Japanese encephalitis virus-associated microglia greatly contribute to endothelial cell death, an important component of the blood brain barrier integrity. Importantly, Tumour Necrosis Factor-related apoptosis inducing ligand and receptors represents a promising therapeutic target preventing microvascular endothelial cell death after neuroinvasion.